Improved methods for genetic manipulation of the alkaliphile Halalkalibacterium halodurans - Wencker, Freya D. R.; Lyon, Seth E.; Breaker, Ronald R. (Frontiers in Microbiology, 2024)
An improved approach was developed for the genetic manipulation of the Gram-positive extremophile Halalkalibacterium halodurans (formerly called Bacillus halodurans). We describe an allelic replacement method originally developed for Staphylococcus aureus that allows the deletion, mutation, or insertion of genes without leaving markers or other genetic scars. In addition, a protocol for rapid in vitro plasmid methylation and transformation is presented. The combined methods allow the routine genetic manipulation of H. halodurans from initial transformation to the desired strain in eight days. These methods improve H. halodurans as a model organism for the study of extremophiles.